(untitled) (European Journal of Economics, Finance and Business Development, 2025)
Real-time tourist route planning is increasingly vital in modern tourism, necessitating algorithms that adapt to dynamic conditions like traffic and user preferences. This study implements and evaluates two heuristic algorithms—genetic algorithms (GA) and simulated annealing (SA)—for real-time route optimization, using Samarkand, Uzbekistan, as a case study, benchmarked against Dijkstra’s algorithm. for hybrid approaches and real-world validation in heritage tourism contexts.